Comparative study on the biomass yield, chemical composition and in-sacco dry matter degradability of different cultivars of triticale fodder (Bangladesh Journal of Animal Science, 2012)
An experiment was conducted to determine the biomass yield, chemical composition and in-sacco dry matter (DM) degradability of 10 cultivars (WRF-7, TSN-111, TYT-03, TYT-05, TYT-06, TYT-08, TYT-12, ITYN-10, ITYN-14 and ITYN-15) of triticale fodder. The fresh yield of different cultivars of triticale was ranged from 5.03 to 6.85 (t/ha). The organic matter (OM), crude protein (CP), acid detergent fibre (ADF), neutral detergent fibre (NDF), calcium (Ca) and phosphorus (P) contents of different cultivars of triticale were found 89.62 to 91.78 %, 21.34 to 25.99 %, 23.09 to 29.99 %, 46.77 to 50.80 %, 0.42 to 0.61 % and 0.33 to 0.41 %, respectively. The yield of DM and CP of different cultivars of triticale were varied from 0.77 to 1.44 (t/ha) and 0.193 to 0.351 (t/ha), respectively. Among different triticale cultivars the highest OM and CP contents were found in TYT-12 (91.78 %) and ITYN-10 (25.99 %), respectively. The highest NDF and ADF contents were found in ITYN-14 (50.80 %) and TYT-05 (29.99 %), respectively among different cultivars. The contents of Ca and P in ITYN-10 (0.61 %) and ITYN-14 (0.41 %), respectively were found to be the highest among the cultivars. Potential DM degradability observed in different cultivars of triticale was higher in ITYN-14 and TYT-05 (84.81 and 81.88 %, respectively) compared to others and relatively poor degradability was found in TSN-111 and TYT-03 (60.74 and 61.35 %, respectively). Therefore, it may be concluded that, the cultivar ITYN-10 will be the promising one due to comparatively higher fresh yield, organic matter (OM), crude protein (CP), neutral detergent fibre (NDF), calcium (Ca) and phosphorus (P) content and less acid detergent fibre (ADF) fraction cultivated for fodder production in Bangladesh.http://dx.doi.org/10.3329/bjas.v41i1.11972